Exploring environmental consideration of sri lankan context - Indrani, M.W.; Wickremasinghe, G.; Naidoo, J.M. (University of Jaffna, 2019)
Decades ago environmental costs were not identified or accounted for by businesses, assuming that environmental costs were very low. However, of late, due to environmental concerns, there has been a steep rise in environmental costs, which has raised many environmental issues. In the sense, this study focuses on to recognise Sri Lanka’s initiatives towards protecting the environment by formulatingand enacting legislation, standards, policies and procedures.This study thus, examined environmental issues/ challenges facing Sri Lanka, and then investigated actions/ strategies taken by respective authorities to protect the environment.In this attempt, the researcher reviewed documents, training prospects, and literature while accessing environmentallegislation i.e. National Environmental Act (NEA). Moreover, the researcher conducted discussions and semi-structured interviews with officials of governmentinstitutions such asCentral EnvironmentalAuthority (CEA), Sri Lanka Standards Institution, Sri Lanka Accreditation who engage ininitiatingandimplementingenvironmental legislation, standards and relatedactivities.Then, using thematic analysis and content analysis techniques, qualitative data are analysed. The findings show that, aside from global pressure, Sri Lanka itself has realised the importance of protecting the environment and being taking necessary measures whilst development projects and industrial activities are in train. This can further be confirmed by reviewing environmental-related laws, regulatory measures and SLS ISO EMS standards that are structured and practised in Sri Lanka for environmental protection. Of these, the NEA is the most important umbrella law for addressing a variety of environmental matters; other laws deal with specific aspects of the environment. The CEA is the key central government body empowered by the NEA to regulate for preserving the environment and minimising pollution.There is room for future researchers to investigate the extent to which industries comply with environmental legislation and thus,allied consequences to the society, and also to explore the appropriateness and adequacy of legislation, standards, policies and procedures prescribed in the Sri Lankan context to protect the environment.
Keywords: Environmental pollution; Environmental protection; Legislation; NEA; CEA